Utilization Of Industrial Waste Derived Ashes As Filler In Acrylonitrile-Butadiene-Styrene Composite - Jansar, Muhammad Faiz (2019)
Industrial wastes such as fly ashes (FA) and palm oil fly ashes (POFA) can cause environmental pollution if not properly managed. In order to reduce the impacts to the environments, industrial waste can be recycled and used as reinforcing filler in polymer based composite. Acrylonitrile butadiene styrene (ABS) is an interesting polymer that can be used as polymer matrix due to its wide applications in various sectors. Addition of industrial waste as filler into ABS can also reduce the usage of ABS while enhancing the mechanical and physical properties of the composite. The purpose of this research is to assess the mechanical and physical properties of ABS filled with industrial waste filler in dry condition. To fabricate the ABS based composites, melt mixing method was used to compound industrial waste particle, i.e., palm oil fuel ash and fly ash with ABS. The tensile, flexural, impact and physical testing have been performed to assess the effects of FA and POFA addition on the properties of ABS. Scanning electron microscope (SEM) was used to study the surface morphology of the composites as to analyse the effect of different amounts and types of filler toward the behaviour of the ABS composites. It has been found that for mechanical properties, POFA filled ABS gives better result than that of FA, but for physical properties FA addition gives better result than POFA addition.